Electric Diffusion of Mono and Polydisperse Polarizable Particles in an Electric Field. (1992) - Zimmels, Y.
Abstract : Thermodynamic analysis of nonuniform dispersion of electrically polarizable particles in electric fields is presented. Extensive and intensive energy formulations are used to derive forces that generate electric diffusion and the corresponding diffusion coefficients. Results obtained for monodisperse systems are extended to polydisperse particle mixtures, and transformation of diffusion coefficient from the fluid to the dispersion frame of reference is provided. Finally, differential diffusion of polydisperse particles can constitute the basis for their separation in electric fields.